2020
DOI: 10.1002/ece3.6278
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing pollination is more effective than increased conventional agriculture inputs for improving watermelon yields

Abstract: Agricultural practices to improve yields in small‐scale farms in Africa usually focus on improving growing conditions for the crops by applying fertilizers, irrigation, and/or pesticides. This may, however, have limited effect on yield if the availability of effective pollinators is too low. In this study, we established an experiment to test whether soil fertility, soil moisture, and/or pollination was limiting watermelon (Citrullus lanatus) yields in Northern Tanzania. We subjected the experimental field to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
1
12
1
2
Order By: Relevance
“…It was reported that growing watermelon decreased soil fertility [45], but we did not find a general pattern in this regard. WR slightly increased N, P and K levels but marginally or significantly decreased organic matter level in the soils compared to FR and RR (Table 3).…”
Section: Pr Is Worth Implementing On the Basis Of Rice Production Benefitscontrasting
confidence: 98%
“…It was reported that growing watermelon decreased soil fertility [45], but we did not find a general pattern in this regard. WR slightly increased N, P and K levels but marginally or significantly decreased organic matter level in the soils compared to FR and RR (Table 3).…”
Section: Pr Is Worth Implementing On the Basis Of Rice Production Benefitscontrasting
confidence: 98%
“…Conventional agricultural practices such as fertilizer and pesticide application, irrigation and genetic modification are used to enhance productivity growth or improve yield. However, for pollinator-dependent crops, effective pollination services overtake these conventional practices in improving crop production in terms of both quantity and quality (Klein et al 2015, Hünicken et al 2020, Sawe et al 2020. For instance, the yield of watermelon (Citrullus lanatus) improves when honey bee colonies are enhanced compared to when conventional factors such as soil fertility and moisture are improved under the limited availability of honey bees (Sawe et al 2020).…”
mentioning
confidence: 99%
“…This is surprising given that pesticides are used to increase yield by, among other things, enhancing individual apple quality. Although our sampling effort may have been too small (e.g., 30 apples of one variety per orchard) to detect an effect, other studies in cucumber and watermelon cropping systems also failed to find a relationship between crop yield and pesticide use [ 87 , 88 ]. In fact, even though cucumber yields were greatly improved when pollination was increased, they were not enhanced when pesticides were used for pest control [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, even though cucumber yields were greatly improved when pollination was increased, they were not enhanced when pesticides were used for pest control [ 88 ]. Similarly, while increased use of fertilizers and irrigation did not increase watermelon yields, adequate pollination did [ 87 ]. Furthermore, we found a relationship with apple weight, but not apple diameter.…”
Section: Discussionmentioning
confidence: 99%